1985
DOI: 10.1128/mcb.5.4.797
|View full text |Cite
|
Sign up to set email alerts
|

Transcription from the polyoma late promoter in cells stably transformed by chimeric plasmids.

Abstract: We have examined the expression of chimeric plasmids containing coding sequences for the herpes simplex virus thymidine kinase (tk) gene or the TnS gene for neomycin resistance (neo) linked to the late promoter of polyoma DNA. Although polyoma late genes are generally not expressed in transformed cells containing only integrated viral DNA molecules, rat tk-or wild-type cells transfected with the tk-or neo-containing plasmids were capable of growing in medium containing either hypoxanthine-aminopterin-thymidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 55 publications
(43 reference statements)
1
49
0
Order By: Relevance
“…The importance of these sequences in the control of polyoma early gene activity and viral DNA replication is clearly documented. However, it is not known whether late gene expression also depends on enhancers, since a significant level of viral late expression during lytic infection or in virus-transformed cells requires extrachromosomal virus DNA replication (16,35,53). Replication is dependent on the expression of the early gene for the viral large T antigen (3,21,53) and, as noted above, requires a functional enhancer element (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these sequences in the control of polyoma early gene activity and viral DNA replication is clearly documented. However, it is not known whether late gene expression also depends on enhancers, since a significant level of viral late expression during lytic infection or in virus-transformed cells requires extrachromosomal virus DNA replication (16,35,53). Replication is dependent on the expression of the early gene for the viral large T antigen (3,21,53) and, as noted above, requires a functional enhancer element (14).…”
mentioning
confidence: 99%
“…Also shown are regions duplicated, deleted, and mutated in naturally occurring variants of polyomavirus (49) or in variants capable of growth in F9 (20,50) (51). scripts have heterogeneous initiation sites (11,35,54) (15) boxes that do form part of the polyoma early transcription unit (29,30). We considered it therefore of interest to determine whether the same sequences within the regulatory region regulate the levels of both early and late transcription.…”
mentioning
confidence: 99%
“…GM Transfections were carried out with the calcium phosphate precipitation protocol (Sambrook et al, 1989). CHO cells were transfected with 91023b-flg, 91023b-bek, MomFR3SV, or LTR2HX in association (10:1, wt:wt) with pCB7 (Kern and Basilico, 1985) and selected with 250 ,tg/ml of G418 (Sigma). Both CHO and GM 7373 cells were transfected with pCEP4-flg 1.2 and selected with 500 or 200 ,tg/ml of hygromycin B (Boehringer Mannheim GmbH, Mannheim, Germany), respectively.…”
Section: Cell Culturesmentioning
confidence: 99%
“…(ii) An enhancer region, originally defined as the 244 bp between the BcII (bp 5021) and PvuII (bp 5264) restriction enzyme sites (17,81), has been subdivided into two unrelated but functionally redundant elements, enhancer A and enhancer B, both of which are capable of stimulating transcription of heterologous genes in an orientation-and position-independent manner (42). Studies with gel retention and nuclease mapping assays have identified several cellular protein factors that bind specifically to the B enhancer (7,26,70 (9,38) and in vivo (2,32,40) and that at least some of the elements of the polyomavirus early promoter, including portions of the enhancer, may regulate the levels of transcription from the late promoter of that virus (8,13,(52)(53)(54).…”
mentioning
confidence: 99%